2016
DOI: 10.1016/j.gene.2015.11.052
|View full text |Cite
|
Sign up to set email alerts
|

Protein kinase A catalytic subunit isoform PRKACA; History, function and physiology

Abstract: Our appreciation of the scope and influence of second messenger signaling has its origins in pioneering work on the cAMP-dependent protein kinase. Also called protein kinase A (PKA), this holoenzyme exists as a tetramer comprised of a regulatory (R) subunit dimer and two catalytic (C) subunits. Upon binding of two molecules of the second messenger cAMP to each R subunit, a conformational change in the PKA holoenzyme occurs to release the C subunits. These active kinases phosphorylate downstream targets to prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
135
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 164 publications
(151 citation statements)
references
References 128 publications
0
135
0
3
Order By: Relevance
“…Significantly represented networks featured proteins previously implicated in ARMS biology (GSK3b, MDM2, CDKN1A, CDKN2A, IGF1R)4344454647, proteins involved in immune evasion and tumor metastasis (CXCL8, CSF1, IFNAR1, CCR2, CASR)4849505152, stemness (SOX2, POU5F1)5354, tumor cell proliferation and invasion (YBX1)41, or have been associated with other tumor types with a possible role in tumor biology (PRKACA, MYO1C, BRINP3)555657. The finding of the miRNA networks targeting proteins involved in stemness, immune evasion and metastasis, enriched in ARMS but not ERMS exosomes, suggests that paracrine signaling via exosomes may have differential effects on mediating the known aggressive behavior of ARMS.…”
Section: Discussionmentioning
confidence: 99%
“…Significantly represented networks featured proteins previously implicated in ARMS biology (GSK3b, MDM2, CDKN1A, CDKN2A, IGF1R)4344454647, proteins involved in immune evasion and tumor metastasis (CXCL8, CSF1, IFNAR1, CCR2, CASR)4849505152, stemness (SOX2, POU5F1)5354, tumor cell proliferation and invasion (YBX1)41, or have been associated with other tumor types with a possible role in tumor biology (PRKACA, MYO1C, BRINP3)555657. The finding of the miRNA networks targeting proteins involved in stemness, immune evasion and metastasis, enriched in ARMS but not ERMS exosomes, suggests that paracrine signaling via exosomes may have differential effects on mediating the known aggressive behavior of ARMS.…”
Section: Discussionmentioning
confidence: 99%
“…(29). In addition, circulating PRKACA has been detected in the sera of patients affected by carcinomas of the colon, kidney, rectum, prostate, lung, adrenal gland, as well as those with lymphomas (30)(31)(32).…”
Section: Del Gobbo a Et Almentioning
confidence: 99%
“…Several studies have suggested that PKA-C may exhibit kinase activity without leaving PKA-R (Johnson et al, 1993; Smith et al, 2013; Yang et al, 1995). However, the vast majority of the literature indicates that PKA-C is released from the AKAP/PKA-R complex during physiological elevations of cAMP concentration (Beavo et al, 1974a; Buxton and Brunton, 1983; Francis and Corbin, 1994; Johnson et al, 2001; Turnham and Scott, 2016). Liberated PKA-C is generally viewed as a cytosolic protein because of its high solubility (Johnson et al, 2001).…”
Section: Introductionmentioning
confidence: 99%